The Effect of Applying Group Investigation Method on Vocational High School Students’ Reading Comprehension - Devi Syarifah Septiana; Budi Setyono; Zakiyah Tasnim (EFL Education Journal, 2021)
This experimental research aimed to discover the effect of applying Group Investigation Method on vocational high school students’ reading comprehension. The participants were the eleventh grade students of SMK Negeri 1 Jember. The research participants was divided into two groups: experimental and control groups. The instrument used to collect the data was reading comprehension test. Product Moment formula was applied to measure the reliability of the reading test. The reliability coefficient of the reading test was 0.70, meaning that the reading test was adequately reliable. The data were analyzed by using t-test formula. The result of analysis revealed that the scores of reading test for the students in the experimental group were significantly different from the one in the control group at the significant level of 0.05. The t-test results indicate that applying Group Investigation Method significantly affected the students’ reading comprehension. It is suggested that English teachers apply Group Investigation Method to teach and enhance students’ reading comprehension.